DISKURSUS PAJAK DAN ZAKAT - Yuli Afriyandi (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2014)
The problem of tax and tithe (zakat) often make a controvertion in Islamic countries. This is because Islam in Rasulullah era never charged a tax to the Moslem, and only charge zakat. Beside the obligation of tax is charged to the non-Moslem people that live in the Islamic era or Islamic authority. The practice of collecting tax (jizyah and kharaj) in Nabi SAW era was done by the collector who had a dualism, that is as a zakat collector and also tax. This policy always continued to the next era. Then in era of Umar bin Abdul Aziz made a new reformation and restructured the system of tax. Now, a longing with the development of era, the study of zakat and tax including the applicating not only in Islamic countries but also non Islamic countries makes a controvertion. The thought that apperars is how the country must place zakat and tax in order to both have a connection. Indonesia, as a country with the great quantity of Islamic people in the world has a facilitated the obligation of tax to the Islamic people, with has releashed the regulation about zakat by the government. But in implementing there are many obstacles. The truly, tax and zakat are two different terms from source side or basic of their collection, but it is as same as the characteristic as a effort to take or pick up the wealth form society for social interest. Zakat for interest has been regulated by religion or Allah SWT whereas tax is used to interest that has regulated by country through valid democration process. The difference of implementing both becomes problem when in particular side there is simmilarity, that is both has a same way obligatory to pay by society. Tax is forced by state’s law, but zakat is forced by God. So that in the system of islamic public finance, zakat and tax must be placed as a different acceptance in a principe, but has a same goal. If it is based on nash-nash, it can be concluded that that nash is valid there is two obligations for Islamic people (particularly Indonesian Moslem), that is obligation to fufill zakat and tax at once.